Statistical theories of income and wealth distribution - Anindya S. Chakrabarti; Bikas K. Chakrabarti (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
The distributions of income and wealth in countries across the world are found to possess some robust and stable features independent of the specific economic, social and political conditions of the countries. We discuss a few physics-inspired multi-agent dynamic models along with their microeconomic counterparts, that can produce the statistical features of the distributions observed in reality. A number of exact analytical methods and solutions are also provided.
Keywords: C31; D51; C00; 330; Personal Income; Wealth and Their Distributions; Exchange and Production Economies; Einkommensverteilung; Vermögensverteilung; Statistische Verteilung; Tauschwirtschaft; Agent-based Model; Theorie